Effects for the incorporation of five-atom thioacetamido nucleic acid (TANA) backbone on hybridization thermodynamics and kinetics of DNA duplexes - Kaur, Harleen; Arora, Amit; Gogoi, K.; Solanke, P.; Gunjal, Anita D.; Kumar, Vaijayanti A.; Maiti, Souvik (Journal of Physical Chemistry B, 2009)
Thermodynamic studies of nucleic acids serve not only to widen our understanding on the nature and strength of forces that stabilize nucleic acids in a myriad of structural states they assume but also to facilitate the development of databases that could be used to predict the stability and selectivity of probe/primer-sets required in a broad range of nucleic acid-based diagnostic and therapeutic protocols. In the current study, we investigated the effect of a novel, backbone-modified ``thioacetamido linkage'' (TANA) on thermodynamics of hybridization, binding kinetics, and conformation of a DNA duplex. The modification comprises of an extended five-atom amide (N3'-CO-CH(2)-S-CH(2)) linker, as opposed to four-atom phosphodiester linker backbone present in DNA. One to three TANA-substitutions have been introduced in the linker backbone of two thymidine residues of one of the strand of the DNA duplex. Using spectroscopic and calorimetric techniques, we observed that TANA destabilizes the DNA helix by lowering the favorable enthalpy parameter of duplex formation. TANA center dot DNA duplexes were found to adopt a conformation toward an A-type duplex as shown by circular dichroism spectroscopy studies. Analysis of differential scanning calorimetry data indicated a nonzero heat capacity change, Delta C(p), accompanying the duplex formation. The average Delta C(p) change per duplex was found to be 832.5 cal mol(-1) K(-1), giving an average base-pair change of 59.5 cal (mol of base pairs)(-1) K(-1). Hybridization kinetic measurements using surface plasmon resonance indicated a decrease in binding affinity parameter (K(A)) that originates from higher dissociation rate constants (k(d)). Furthermore, optical melting studies showed that increasing the number of modifications results in a modest change in the number of counterions taken up during duplex formation.